2015
DOI: 10.1007/s00348-015-1995-6
|View full text |Cite
|
Sign up to set email alerts
|

Drag of a turbulent boundary layer with transverse 2D circular rods on the wall

Abstract: between the boundary layer developing over this wall and the smooth-wall turbulent boundary layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…This result has been further corroborated for a turbulent boundary layer by the DNS study of Lee & Sung (2007). Experimentally, Kamruzzaman et al (2015) showed that the pressure drag contributed almost totally to the total drag on a rod-roughened wall with λ/k = 8. Removing the viscous term from (2.8) amounts to dropping (2.9h), while all other conditions remain valid.…”
Section: Rough Wallsupporting
confidence: 63%
See 2 more Smart Citations
“…This result has been further corroborated for a turbulent boundary layer by the DNS study of Lee & Sung (2007). Experimentally, Kamruzzaman et al (2015) showed that the pressure drag contributed almost totally to the total drag on a rod-roughened wall with λ/k = 8. Removing the viscous term from (2.8) amounts to dropping (2.9h), while all other conditions remain valid.…”
Section: Rough Wallsupporting
confidence: 63%
“…In the present study, the situation is different as the cylinders are attached to a wall. However, recent observations by Kamruzzaman et al (2015) showed that the pressure distribution around a single cylinder element remained essentially identical over a range of Re, which is consistent with approximately constant C d . For smooth walls, the spatial averaging is not required and thus the dispersive Reynolds stress and the drag forces vanish from (2.1b).…”
Section: Theoretical Considerationssupporting
confidence: 55%
See 1 more Smart Citation
“…By correlating them together, we can get an estimated value of the equivalent sand grain roughness height, which is a direct function of the roughness function. 7; TBL Data over rods from Djenidi [1] and TBL data over rods from Kamruzzaman [5]. The equation used to predict the k s :…”
Section: Roughness Functionmentioning
confidence: 99%
“…The roughness function as a function of equivalent sand grain roughness height, normalised by inner length scale U τ /ν Figure 7 shows the roughness function ∆U + as a function of the equivalent sand grain roughness k + s in a fully rough regime. The results presented are the measured k + s from the velocity profiles over the rough surfaces; the predicted k + s from the k sk and ES, which have a larger marker size in figure7; TBL Data over rods from Djenidi[1] and TBL data over rods from Kamruzzaman[5]. The equation used to predict the k s :…”
mentioning
confidence: 99%